The Political Economy of Memory: Heritage Gentrification and Domicide by Rent Seeking - Clark, Eric (ICONARCH International Congress of Architecture and Planning, 2017)
As extensions of our proprioceptive bodies, places embody memory. Place-bound memories are the very foundation of hope. Being displaced consequently entails immense burdens on the displaced: practical, social, economic, cultural and existential. The transformative powers of finance and property capital generate escalating creative destruction of urban environments by reducing place to a commodity and fastidiously putting land to its ‘highest and best use’, displacing millions of people in the process in order to secure potential returns on ‘investment’. One would think that conservation of heritage could function as a source of friction, a bulwark of inertia protecting (in the words of Karl Polanyi) ‘habitation against the juggernaut, improvement’. This is also part of the story in some instances. But heritage is often controlled, coopted, staged and managed by dominant powers as a key resource in the orchestration of processes of heritage gentrification. The contradictions and tensions underlying heritage gentrification extend beyond straightforward matters of rivalling memories and heritages struggling for recognition and control over urban space, although this is part of the story: whose heritage? Even where there is no apparent contestation over place-bound heritage (this is often claimed, but seldom the case), there are other tensions at play. What happens when heritage is treated as a financial asset? How is heritage speculatively deployed to enhance potential land rents? How does the capture of rent gaps – in part created by speculation in myth and memory – wreak havoc on the homes and memories of those displaced by heritage gentrification? How is heritage paradoxically put to use as a tool for domicide and memoricide? This paper presents an understanding of heritage gentrification as largely driven by processes of financialisation and rent seeking, and in turn as driver of incalculable suffering stemming from the devastating events of domicide, memoricide and topocide.